Elevated levels of per- and polyfluoroalkyl substances in Cape Fear River Striped Bass (Morone saxatilis) are associated with biomarkers of altered immune and liver function. (March 2020) - Guillette, T.C.; McCord, James; Guillette, Matthew; Polera, M.E.; Rachels, Kyle T.; Morgeson, Clint; Kotlarz, Nadine; Knappe, Detlef R.U.; Reading, Benjamin J.; Strynar, Mark; Belcher, Scott M.
Highlights: PFOS was detected in all samples and had elevated levels in Cape Fear River fish. Cape Fear River fish had detectable levels of a novel PFAS (Nafion byproduct 2). PFOS positively associated with higher lysozyme activity in Cape Fear River fish. Cape Fear River fish have 40 times higher PFAS body burden than a reference site. Abstract: Per- and polyfluoroalkyl substances (PFAS) are anthropogenic chemicals of concern that persist in the environment. Environmental monitoring revealed high concentrations of hexafluoropropylene oxide dimer acid (HFPO-DA) and other novel PFAS in the lower Cape Fear River; however, there is limited information on PFAS exposures and effects of this contamination on aquatic biota. Serum concentrations of 23 PFAS in Striped Bass ( Morone saxatilis ) from the Cape Fear River (n = 58) and a reference population from an aquaculture laboratory on the Pamlico/Tar watershed (n = 29) were quantified using liquid chromatography and high-resolution mass spectrometry, and correlations between PFAS concentrations and health-related serum biomarkers were evaluated. Perfluorooctane sulfonate, the predominant PFAS in Cape Fear River Striped Bass serum, was detectable in every sample with serum concentrations reaching 977 ng/mL. Perfluorononanoic and perfluorodecanoic acid were also detected in all samples, with perfluorohexanesulfonic acid present in >98% of the samples. HFPO-DA (range <0.24–5.85 ng/mL) and Nafion byproduct 2 (range <0.2–1.03 ng/mL) were detected in 48% and 78% of samples, respectively. The mean total PFAS concentration found in domestic Striped Bass raised in well-water under controlled aquaculture conditions was 40 times lower, with HPFO-DA detected in 10% of the samples, and Nafion byproduct 2 was not detected. The elevated PFAS concentrations found in the Cape Fear River Striped Bass were associated with biomarkers of alterations in the liver and immune system.